Parasitoid fruit flies Bactrocera mcgregori (Diptera: Tephritidae) from Tanah Laut Regency and Banjarbaru South Kalimantan - M. Indar Pramudi; Lyswiana Aphrodyanti (TROPICAL WETLAND JOURNAL, 2019)
This study aims to identify and determine the parasitic level of Bactrocera mcgregori parasitoid from melinjo fruit (Gnetum gnemon) from Tanah Laut district and Banjarbaru Kalimatan Selatan City. The identification results of the three parasitoids showed the characteristics of the Hymenoptera order, the family Braconidae. The three parasitoids are Psytallia flecheri habitus (Silvestri) parasitoid, Psytallia lounsburyi (Silvestri) and Diachasmimorpha longicaudata (Cameron).